Africa towards COP27. Earth Day reflections (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
A hopeful World is wondering whether COP27, to be held next November in Sharm El-Sheikh (Egypt), has the potential to foster the much-needed change of mindset that determined the disillusion of the previous International Conferences organized by the UNFCCC, as the regional mid-term MENA conference on climate change, held last March in Dubai, seemed to stagnate in lamentations, instead of steering into action. In the meantime, Africa is going through an escalation among syndemics, diminished access to food, and local crises fuelled by climate change, whose ticking bomb is rhythmed by floods and droughts, while the new need of the global North for energy supplies could determine economic opportunities but also negative impacts on African decarbonization and mitigating actions. There is a shared concern on whom and how to push for immediate political pressures in order not to lose the little thrust that we had gained.
Keywords: COP27; Africa; MENA; Egypt; climate change; energy supply; access to food; migrations